A rare case of right‐sided infective endocarditis caused by group B Streptococcus complicated with septic knee arthritis and subcutaneous abscess in the lower extremity. Issue 1 (17th September 2019) - Takeda, Shinsuke; Tanaka, Yoshihiro; Takeichi, Yosuke; Hirata, Hitoshi; Tabuchi, Akihiko
Abstract : Background: Several reports have assessed group B Streptococcus (GBS) infections in non‐pregnant cohorts, especially in immunocompromised hosts and patients with severe disease, including diabetes mellitus. Case presentation: We report a rare case of large GBS ‐ associated tricuspid valve infective endocarditis (IE) complicated with septic knee arthritis and s.c. abscess formation in the lower extremity of a non‐i.v. drug user. After confirming the absence of vegetation on transthoracic echocardiography (TTE) at admission, the lower extremity was irrigated, and antibiotic therapy was initiated. One week later, the causes of persistent fever were reinvestigated. The TTE detected a large mass around the tricuspid valve. The cultured GBS was penicillin sensitive. The vegetation completely disappeared without surgery within 4 weeks. Conclusion: When patients with untreated diabetes mellitus have persistent fever and s.c. abscess or septic arthritis, IE is a possible differential diagnosis. Repetitive evaluation by TTE is warranted to avoid this fatal complication. Abstract : We report a rare case of large group B Streptococcus ‐associated tricuspid valve infective endocarditis complicated with septic knee arthritis and s.c. abscess formation in the lower extremity of a non‐i.v. drug user.